The Effect Of Exercise On Elderly People On Blood Pressure Changes In Elderly People With Hypertension At The Tresna Werdha Pagar Dewa Social Institution In Bengkulu Province In 2024 - Lestari, Susi; Murwati, Murwati; Azissah, Danur (Utami Publisher, 2025)
Hypertension in the elderly occurs due to the aging process in the elderly, namely physiological decline that causes the strength of the heart pumping machine to decrease and large arteries lose their flexibility and become stiff and cannot expand when the heart pumps blood through the arteries which results in increased blood pressure. The purpose of this study was to determine the effect of elderly exercise on changes in blood pressure in elderly with hypertension at the Pagar Dewa Werdha Home, Bengkulu Province in 2024. The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used total sampling technique with a sample size of 30 people representing elderly with hypertension at the Pagar Dewa Werdha Home, Bengkulu Province. The results of the univariate test analysis showed that the average value of systolic blood pressure before the intervention was 160.33 and diastolic 88.47. After the intervention, the average value of systolic blood pressure was 136.17 and diastolic 80.50. The results of the bivariate analysis with the Wilcoxon statistical test results obtained a systolic π-value of 0.000 and a diastolic 0.000. There is an effect of elderly exercise on blood pressure in elderly with hypertension at the Pagar Dewa Werdha Home, Bengkulu Province in 2024. Researchers suggest that the Pagar Dewa Werdha Home, Bengkulu Province can increase public knowledge in the form of counseling efforts regarding the effect of elderly exercise on changes in blood pressure in elderly with hypertension.